PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN DAN KEPUASAN PELANGGAN TERHADAP PENJUALAN KARET DI PT. PERKEBUNAN NUSANTARA III (PERSERO) - Bagus Agung Susetiyo; Sya'ad Afifuddin; Sri Fajar Ayu (Universitas Medan Area, 2017)
PT. Perkebunan Nusantara III (Persero) have achieved and increase the level of sales through the provision of best quality rubber accordance to International standards, provide good service and high satisfaction in maintaining and sustaining the consumer in order not to switch to other competitors. The data analysis used is descriptive analysis and multiple linear regression analysis. The result show that product quality, quality of service and customer satisfaction has a positive coefficient sign. This means that the improvement of product quality, service quality and customer satisfaction will increase the level of sales.Kata Kunci: Product, Service, Satisfaction, Quality